Yolk–Shell Nanostructure: An Ideal Architecture to Achieve Harmonious Integration of Magnetic–Plasmonic Hybrid Theranostic Platform. Issue 21 (22nd March 2017) - Lin, Li‐Sen; Yang, Xiangyu; Zhou, Zijian; Yang, Zhen; Jacobson, Orit; Liu, Yijing; Yang, Angela; Niu, Gang; Song, Jibin; Yang, Huang‐Hao; Chen, Xiaoyuan
Abstract : Magnetic–plasmonic hybrid nanoparticles (MPHNs) have attracted great interest in cancer theranostics. However, the relaxivity of the magnetic component is typically reduced by the plasmonic component in conventional core–shell structured MPHNs, due to the presence of a water‐impenetrable coating which severely restricts the proximity of protons to the magnetic portion. To circumvent this issue, yolk–shell structured MPHNs comprising a Fe3 O4 core within a hollow cavity encircled by a porous Au outer shell are designed. As expected, the introduction of hollow cavity between the magnetic and plasmonic portions significantly prevents the decline in relaxivity of the Fe3 O4 core caused by the Au layer. Moreover, in addition to conferring high near‐infrared absorption to plasmonic component, the hollow cavity and the pores in the outer shell can also provide a large storage space and release channels for anticancer drugs. Furthermore, the multicomponent nanoparticles (NPs) still have a compact size of less than 100 nm to ensure efficient tumor accumulation. Taken together, the yolk–shell Fe3 O4 @Au NPs can be regarded as an ideal magnetic–plasmonic theranostic platform for magnetic resonance/photoacoustic/positron emission tomography multimodal imaging and light‐activated chemothermal synergistic therapy. Abstract : Yolk–shell‐structured Fe3 O4 @Au nanoparticles are designed to circumvent the decline in the relaxivity of the magnetic component caused by the introduction of water‐impenetrable plasmonic components, which is unavoidable in traditional core–shell‐structured nanostructures. This feature, in conjunction with their compact size, near‐infrared absorption, and drug‐delivery capability, makes them harmoniously integrated magnetic–plasmonic theranostic nanoplatforms for multimodal imaging and light‐triggered chemothermal synergistic therapy.